Perancangan Vihara Avalokitesvara Makassar dengan Pendalaman Sense of Place oleh Kantor Konsultan Arsitektur Interior Yi-San Studio - Ivany, Ivany; Rahadiyanti, Melania (KREASI, 2024)
The final assignment report, "Designing the Avalokitesvara Monastery in Makassar with a Deepening Sense of Place by Yi-san Studio," contains the interior and architectural design plans for the Avalokitesvara Monastery in Makassar. Designing a monastery with a sense of place aims to create a space that not only functions as a place of worship but can also provide a deep spiritual and emotional experience for its users. In the context of the monastery, a sense of place can be achieved by combining architectural, landscape, and symbolic elements that reflect Buddhist values ​​and teachings. Avalokitesvara Vihara can show the identity of a place of worship that has the characteristics of Buddhist places of prayer in general and provides comfort for users. Additionally, it may draw attention to the Avalokitesvara Vihara and encourage people to visit for prayer. The application of the design is realized by the use of flower and animal ornaments, which symbolize the unity of nature and living things; the colors are typical of Chinese architecture; the square ornament on the door symbolizes life in a better direction; the front door is also made with a model that is very typical of traditional houses in China; and the use of natural materials to provide a comfortable atmosphere during worship. The design of the Avalokitesvara Vihara also applies the New Normal design as a response to the COVID-19 pandemic, namely by giving aloe vera plants to help reduce toxins in the air and increasing openings to obtain natural air circulation.